Autistic youth in 3D game‐based collaborative virtual learning: Associating avatar interaction patterns with embodied social presence. (30th July 2018) - Wang, Xianhui; Xing, Wanli; Laffey, James M.
Abstract: This study examines interaction patterns in a series of game activities for learning social skills by autistic youth in a 3D game‐based collaborative virtual learning environment (CVLE). Researchers studying collaborative learning have indicated the importance of social interactions and social presence. However, few studies have examined the relationship of avatar social interactions with embodied social presence in a 3D game‐based CVLE. Specifically, we examined avatar‐mediated verbal and nonverbal interactions by autistic youth in iSocial, a game‐based 3D CVLE for developing social competencies. How are avatar‐mediated verbal and nonverbal social interactions related to the extent of embodied social presence? Building on prior studies on embodied social presence (ESP) theory and the verbal and nonverbal social interaction framework, this paper aims to explore the link between the combination of verbal (appropriate and inappropriate) and nonverbal (avatar proximity, orientation, joint attention and gesture) interaction patterns and experienced ESP level. We report on the results of 3 cohorts of a total of 11 youth aged from 11 to 14 who were diagnosed with Autism Spectrum Disorder learning in 13 game activities in iSocial. The video data of the participants' screen recordings were analyzed and coded based on the ESP theory and verbal and nonverbal social interaction framework. Through cluster analysis, the results identify distinct patterns of verbal and nonverbal interaction that are associated with different levels of embodied social presence. The findings of this study (1) shed light on the link between social interactions and embodied social presence and (2) provide a deeper understanding of how the unique spatial and visual characteristics of 3D CVLE and the design of game activities in 3D CVLE may transform collaborative learning, especially for autistic youth.